Making space for hybridity: Industrial heritage naturecultures at West Carclaze Garden Village, Cornwall. Issue 113 (July 2020) - Bartolini, Nadia; DeSilvey, Caitlin
Highlights: Geography rejects the nature/culture binary but it still prevails in other fields of practice. We explore the place of industrialised naturecultures in planning and heritage discourses. Regeneration can catalyse the reinscription of industrial objects and ecologies as heritage. Productive ambivalence allows for coexistence of the cultivated and wild, natural and cultural. Abstract: The paper explores the diverse forms of renaturing and reinscription which arise from the materiality of industrial decline and the desire to make space for nature in new peri-urban developments. As productive use is sought for post-operational spaces, remnant industrial objects and ecologies are either removed or incorporated into new landscape narratives and forms. When they are retained, the status of such remnants often remains unstable, as their identities are (re)inscribed through diverse and sometimes competing value frameworks. Instability and ambivalence are particularly pronounced in relation to features that straddle categories of nature and society: nature-culture assemblages produced through both industrial and ecological processes. In this paper, we examine two such assemblages at West Carclaze, Cornwall, in the SW of the UK, a site shaped by the process of china clay extraction and now undergoing redevelopment as a 'garden village'. The paper considers an artificial hill formed of clay-processing waste and a rare bryophyte species which depends for its survival on ongoing industrial process. Both of these objects represent a category which we describe as 'industrial heritage naturecultures' – hybrid entities whose recognition potentially signals a new willingness to accept the blurring of nature-society distinctions in planning and heritage management contexts.